2012 IEEE 14th International Conference on Communication Technology 2012
DOI: 10.1109/icct.2012.6511179
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of UMTS900 and UMTS2100 for rural connectivity in Tanzania

Abstract: Abstract-Rural areas of the developing countries lack Information and Communication Technology (ICT) infrastructures such as access network, also known as last mile connectivity, to deliver ICT services. The lack of connectivity is due to high cost of implementing ICT infrastructures. Wireless technologies are envisioned as candidates for rural connectivity. They are not only easier and faster to deploy but also cheaper than the wired technologies. This paper presents a technoeconomic analysis of two wireless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…Techno-economic analysis (TEA) is defined as a systematic analysis used to evaluate the economic feasibility aimed to recognize opportunities and threats of projects, taking into account the capital, variable (operational), and fixed costs (Simba et al, 2012), as well as benefits. Fixed and annual operating costs are critical parameters in TEA and are key factors for cost estimation, project evaluation, and process optimization (Marouli & Maroulis, 2005).…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…Techno-economic analysis (TEA) is defined as a systematic analysis used to evaluate the economic feasibility aimed to recognize opportunities and threats of projects, taking into account the capital, variable (operational), and fixed costs (Simba et al, 2012), as well as benefits. Fixed and annual operating costs are critical parameters in TEA and are key factors for cost estimation, project evaluation, and process optimization (Marouli & Maroulis, 2005).…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…Registered users can top up their accounts via vouchers and use SMS for their transactions. In [374], a study on the deployment of 3G CDMA deployment over the 900 MHz frequency to provide connectivity in Tanzania showed that the deployment is economically viable. The use of 900 MHz spectrum allows for longer propagation distances to serve rural areas, similarly to the proposition of using CDMA in the 450 MHz in rural Ecuador in [348].…”
Section: Other Countriesmentioning
confidence: 99%
“…Techno-economic analysis is a tool used to reveal the total cost of a process, and can be used for analyzing optimization efficiency of a new process or technology applied in a system. Some common criteria used in techno-economic analysis are cash flow, discounted cash flow, net present value (NPV), internal rate of return (IRR), payback period (PP), and sensitivity analysis [34]. Thus, when related to potential environmental impacts, techno-economic analysis and assessment can be used to identify the most promising technologies that can be applied to the system under study [35].…”
Section: Life Cycle Assessment (Lca) and Techno-economic Analysis (Tea)mentioning
confidence: 99%